The forming of bacteria biofilm from Streptococcus mutans and Aggregatibacter actinomycetemcomitans as a marker for early detection in dental caries and periodontitis - Indah Listiana Kriswandini; Diyatri I; Tantiana; Nuraini P; Berniyanti T; Putri IA (MDPI AG, 2020)
Background: This is an initial study of the biofilm of Streptococcus mutans (S.mutans) and Aggregatibacter actinomycetemcomitans (A.a). S. mutans and A.a are bacteria that cause infection diseases in the oral cavity. These bacteria have the ability to form biofilms. The study of bacterial biofilm proteins was used as an alternative to early prevention for oral infections. It would be used for the purpose of creating a marker for Infection Detection Kit in the oral cavity. Objective: To easily detect caries or Periodontitis with the biofilms of S. mutans and A.a at the early stage. The forming of biofilm proteins from S.mutans and A.a induced with 5% glucose, 5% lactose, 5% soy protein, and 5% iron will be use as a marker for early detection to Dental caries and Periodontitis. Methods: SDS-PAGE electrophoresis technique was used in the study to measure the molecular weight of S. mutans and A.a biofilms induced with 5% glucose, 5% lactose, 5% soy protein, and 5% iron. Results: Biofilm bands of S. mutans and A.a were formed with the various numbers depending on the induction used. These results are early chararterization of biofilm that will beused as a marker for early detection of infectious diseases in oral cavity (Dental Caries and Periodontitis). Conclusions: S. mutans bacteria induced with 5% glucose had one band of biofilm protein, with 5% lactose had four bands of biofilm proteins, and with soy protein had seven bands of biofilm protein, but with 5% iron did not produce any protein bands and neither did A.a.